(untitled) (The Journal of Psychology and Sociology, 2015)
In article problem of early psychodiagnostics of emotional burning out of teacher as a basic component of preservation of psychological health of peda gogical workers are considered. Numerous researches show that the pedagogi cal profession is one of those that are more subject to influence of “burning out”. This is due to the fact that the professional work of teacher is distinguished by very high emotional load. Relevance of the topic of emotional burning out is caused by the increasing requirements from society to the identity of teacher be cause this profession is characterized by huge social importance. Ability to em pathy is recognized as one of the most important qualities of teacher; however, in general, the practical role of emotions in professional activity is contradicto rily estimated. It can be stated that teachers are not prepared for a possible emo tional overload, and appropriate knowledge, skills and personal qualities that is necessary for overcoming of emotional difficulties of the teaching profession are not purposefully formed. The AVEM questionnaire is the multifactorial diag nostic tool, which allows to define the types of human behaviors in situations of professional requirements. At creation of a questionnaire authors proceeded from the assumption that the interaction of the individual with requirements of the professional environment, which promotes mental health and professional development, is defined by three main spheres of the personality: 1. The professional activity which expressed in categories of subjective val ue of activity, professional claims, readiness for power expenses, commitments to excellence during the performing of tasks, and also the ability to maintain the distance between the personal and professional spheres of life. 2. Strategy of overcoming the problematic situations that presented in cat egories of a tendency to refusal from further performance of professional tasks, especially in situations of defeats and failures; active strategy of overcoming difficulties, and also internal balance. 3. The emotional setting to professional activity which expresses by sense of social support, professional success and life satisfaction.